Expresión de la sexualidad e inteligencia emocional: una experiencia educativa para reflexionar - Carballo Vargas, Sonia (2004)
The experience described here is based on a workshop about expressing sexuality and emotional intelligence. The course was held at the Corazon de Maria School, located in the Penitentiary Center for young men. The challenge to free the constructive power that lies within each person is possible only through a type of education that allows him to admit the truth that can be encounter in the ideas of others, to create their own ideas and to have their own criteria that will help them construct and deconstruct any assumption and behave accordingly. The educational process has not ended, and we have a lot of hope for these adolescents. They are very similar to the adolescents of our own families, but it is necessary to remember that their personalities and the opportunities they have had in life are unique; thus, they cannot be seen just like any other teenager we meet every day.